"American Chimera: The Ever-Present Domination of Whiteness, Patriarchy, and Capitalism…A Parable". Issue 9 (28th July 2016) - Montoya, Roberto; Matias, Cheryl E.; Nishi, Naomi W.M.; Sarcedo, Geneva L.
Abstract: In Greek mythology, the Chimera is a fire-breathing monster with three heads: one of a lion, one of a horned goat, and one of a powerful dragon. Of similar construction is the presence of three structures in US society, whiteness, patriarchy, and capitalism, which are overwhelmingly represented, valued, and espoused when examining areas of progress, i.e., family income, poverty rates, high school and college graduation rates, and home ownership. This modern American three-headed beast controls, manipulates, and permeates all aspects of US society irrespective of class, culture, or gender. Using critical race theory and critical whiteness studies, this critically interpretive parable draws from the ways in which whiteness, patriarchy, and capitalism function in social, cultural, economic, and educational spheres. The parable tells the story of Sue Libertad and analyzes how this metaphorical Chimera, despite its ubiquity, silently permeates all aspects of her life. Not until a tragic outbreak occurs, does the hegemony of this chimera erodes and Sue.